2006
DOI: 10.3727/000000006783981954
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Microencapsulated Islets at 400 Days Posttransplantation in the Omental Pouch of NOD Mice

Abstract: The long-term durability of agarose microencapsulated islets against autoimmunity was evaluated in NOD mice. Islets were isolated from 6-8-week-old prediabetic male NOD mice and microencapsulated in 5% agarose hydrogel. Microencapsulated or nonencapsulated islets were transplanted into the omental pouch of spontaneously diabetic NOD mice. Although the diabetic NOD mice that received nonencapsulated islets experienced a temporary reversal of their hyperglycemic condition, all 10 of these mice returned to hyperg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 17 publications
1
45
0
Order By: Relevance
“…A single i.p. injection of MC-SeC promoted body growth in a mouse model of the human Laron syndrome (dwarfism), characterized by mutations in GHR (growth Alginate-based microcapsules have shown long durability in terms of survival of the entrapped cells and have been used in rodents, dogs and monkeys [111][112][113][114]. Moreover, alginate-based microcapsules containing human pancreatic islets have been employed in clinical trials in which they were transplanted i.p.…”
Section: Pre-clinical Studies Using Microencapsulated Secmentioning
confidence: 99%
“…A single i.p. injection of MC-SeC promoted body growth in a mouse model of the human Laron syndrome (dwarfism), characterized by mutations in GHR (growth Alginate-based microcapsules have shown long durability in terms of survival of the entrapped cells and have been used in rodents, dogs and monkeys [111][112][113][114]. Moreover, alginate-based microcapsules containing human pancreatic islets have been employed in clinical trials in which they were transplanted i.p.…”
Section: Pre-clinical Studies Using Microencapsulated Secmentioning
confidence: 99%
“…This study was repeated in 2006, where the same period of normoglycemia was observed in transplant recipients. In addition, when the devices were removed after 400 days, viable islets were recovered with a small percentage of necrotic cells [14]. Aside from agarose, polyethylene glycol-poly lactic-co-glycolic acid (PEG-PLGA) has been used to encapsulate 500-600 IEq islets for syngeneic transplant into streptozotocin (STZ) induced diabetic BALB/c mice, where over half of the recipients achieved normal glucose levels for up to 100 days [15].…”
Section: History Of Animal and Human Trials Of Islet Encapsulationmentioning
confidence: 99%
“…For example, the alginate capsule is made by dropping it into ionic solution (Ca 2+ , Ba 2+ , etc.) [55] and the agarose capsule is made by cooling with shaking [56] . Microcapsules have some advantages in the transportation of oxygen and nutrients because of the smaller distance between the capsule surface and the islet [38] .…”
Section: Shapes Of Encapsulated Isletsmentioning
confidence: 99%
“…In experimental studies, there are many descriptions of positive data on extrahepatic transplantation sites. The Kyoto and other groups [73] succeeded in achieving normoglycemia in diabetic mice by transplantation of encapsulated islets in muscle, subcutaneous tissue [58,[74][75][76] , renal subcapsule [77] and omentum [56] . These may be candidate transplantation sites in the near future because the loss of islets due to IBMIR, the risk of portal hypertension and portal vein thrombosis could be prevented.…”
Section: Ideal Transplantation Site For Encapsulated Isletsmentioning
confidence: 99%